Development of virulence to Meloidogyne incognita on resistant pepper rootstocks - C. Ros Ibáñez; Lee Robertson; Maria del Carmen Martinez-Lluch; Ana Cano-García; Alfredo Lacasa-Plasencia (Spanish Journal of Agricultural Research, 2014)
The root-knot nematode (RKN) Meloidogyne incognita is a major soil parasite of pepper crops in greenhouses in Southeast Spain. Due to the limitations of the use of soil fumigants, grafting plants on resistant rootstocks (R-rootstocks) has become an important alternative to chemical nematicides. The repeated use of R-rootstocks can bring about the selection of virulent populations capable of overcoming resistance. We carried out a six-year investigation on resistant rootstocks in a naturally M. incognita infested greenhouse, and found that two successive years of growing plants grafted on R-rootstocks Atlante (ATL) were sufficient to overcome resistance (galling index 1.5 and 5.6 in the first and second years respectively). A large variability was observed between several R-rootstocks. Two R-rootstocks (C19 and Snooker) behaved like ATL while two others (Terrano and DRO 8801) were not infected by RKN. Laboratory studies with the same R-rootstocks, inoculated with two nematode isolates (avirulent and virulent against ATL) confirmed the greenhouse results, indicating that some rootstocks may be infested by virulent populations and others may not. It suggests that different R-genes, which are differentially overcome by RKN, have been introgressed into the rootstocks. This may have consequences for the management of resistant rootstocks in the field.